Marvin McArthur and Christine 'Tiny' Albanese
Photograph of Marvin McArthur and Christine 'Tiny' Albanese standing in suit and evening dress. Christine 'Tiny' Albanese is adjusting Marvin McArthur's tie. In front yard of 780 Irene Street.